2005
DOI: 10.1021/es049096d
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Net Mercury Methylation Rates Following Iron Amendment to Anoxic Wetland Sediment Slurries

Abstract: The rate of mercury methylation in anoxic wetland sediments is affected by the concentration of bioavailable complexes between Hg and sulfide. Previous research with pure bacterial cultures has shown that addition of ferrous iron reduces the net rate of mercury methylation by decreasing the concentration of dissolved sulfide. To assess the possibility of using this approach to decrease net mercury methylation in restored and constructed wetlands, laboratory experiments were conducted by adding Hg(II) and Fe(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 32 publications
(36 reference statements)
1
39
0
Order By: Relevance
“…One approach is to apply a chemical amendment that has the potential to reduce the concentration of Hg(II) available for Hg(II)-methylation by reduction to volatile elemental Hg(0) (Vernon and Bonzongo, 2014). Another approach is to add a complexation agent that has the potential to reduce the concentration of sulfides that are reported to facilitate Hg(II)-methylation by the formation of neutral mercury sulfide (HgS) complexes (Mehrotra and Sedlak, 2005). One of the more common approaches to remediation is to add a sorbent to adsorb Hg(II) and MeHg, thus decreasing the concentrations of the MeHg precursor and product (Weisener and others, 2005;Vernon and Bonzongo, 2014.…”
Section: Potential Remediationmentioning
confidence: 99%
“…One approach is to apply a chemical amendment that has the potential to reduce the concentration of Hg(II) available for Hg(II)-methylation by reduction to volatile elemental Hg(0) (Vernon and Bonzongo, 2014). Another approach is to add a complexation agent that has the potential to reduce the concentration of sulfides that are reported to facilitate Hg(II)-methylation by the formation of neutral mercury sulfide (HgS) complexes (Mehrotra and Sedlak, 2005). One of the more common approaches to remediation is to add a sorbent to adsorb Hg(II) and MeHg, thus decreasing the concentrations of the MeHg precursor and product (Weisener and others, 2005;Vernon and Bonzongo, 2014.…”
Section: Potential Remediationmentioning
confidence: 99%
“…Warner et al (67) demonstrated that freshwater sediments with iron reduction as the dominant process had methylation potentials similar to those of sediments in which sulfate reduction was the dominant terminal electron accepting process. Recent studies (46) showing stimulation of methylation by low concentrations of iron (0.3 and 3.0 mM) suggest (assuming some oxidation of the added ferrous chloride) that methylation by iron-reducing bacteria is also important in marine sediments. These increased methylation rates may be due to increases in the bioavailability of mercury for methylators in general, via dissolution of iron colloids or via electron acceptor stimulation of methylation by metal-reducing bacteria.…”
Section: Fig 2 Cell Density (Circles) and Methylmercury (Mehg) Concmentioning
confidence: 99%
“…The formation of Fe plaque on roots significantly inhibited the uptake of As by rice, under both glasshouse (Chen et al 2005) and paddy field conditions (Garnier et al 2010). It has also been reported that adding ferrous iron to sulphidic wetland sediments decreased Hg bioavailability and net methylation due to a decrease in sulphide activity and a concomitant decrease in the concentration of dissolved mercury (Mehrotra et al 2003;Mehrotra and Sedlak 2005). However, the exact effects of ROL and Fe plaque formation on Hg and MeHg uptake by rice plants have not been reported.…”
Section: Introductionmentioning
confidence: 99%